The Return of the Native, But Not Alone! in Tishani Doshiâ€™s The Pleasure Seekers and Shilpi Somaya Gowdaâ€™s Secret Daughter - Bhattacharya, Ramakrishna Mission Residential College, West Bengal, India, Sajalkumar (Asiatic: IIUM Journal of English Language and Literature, 2012)
Transnationalism has failed to become an unqualified boon because of the threats of neo-colonialism ingrained in it. This has put the Expatriate Indian novelists in an even more uncomfortable position lately, as a feeling of otherisation continues to haunt them at both entry and exit points. Hence, to resist the threats of neocolonisation and xenophobia, to overcome feelings of aloofness and loss incurred by the diasporic movement, and finally, to reaffirm their closeness to India, a clutch of contemporary Expatriate novelists have â€œreturnedâ€ to the site of Indian family. In most cases, the presented picture has been utopian, but in its exhilarating nature and expansiveness, the site can, as the writers have attempted in showing, be effectively projected as a succour to the fractured life of the West. Consequently, the site has always remained an object of desire to all those who have been dislodged from it. My paper aims to read Tishani Doshiâ€™s The Pleasure Seekers (2010) and Shilpi Somaya Gowdaâ€™s Secret Daughter (2010) to explore this issue.